Unveiling Excellence in Service: from Exceptional Staff to Exceptional Guest - Raditya Prayogi, I Gusti Bagus; Artana, I Komang Yogi; Gunawan, I Made Chandra; Widnyana, I Made Erik; Adisurya, I Made Joviantha; Ananda Suaja, I Made Yudista (Westscience Press, 2024)
This research aim at exploring excellence service in hospitality industry. The research method was deep interview with the management of AH hotel and resort. The focus was unveiling service excellence on the pivotal role of exceptional staff in catering to the needs of exceptional guests. Drawing upon literature on service excellence, staff engagement, and guest satisfaction, the abstract highlights the importance of personalized experiences and genuine dedication in surpassing guests' expectations. The result were through a commitment to understanding guests' preferences and fostering a culture of excellence among staff, hotels can elevate the guest experience and cultivate long-term loyalty. The uniqueness of excellence service at the accounting department lies in its precision, efficiency, personalized financial solutions, proactive management, and transparent communication, all of which contribute to a seamless guest experience and the hotel's success. The symbiotic relationship between excellence staff and excellence guests in the pursuit of service excellence. Hotel management is advised to constantly remind employees about the importance of maintaining service quality to avoid complaints from management, colleagues, and hotel guests.